The Urgency of Counter-Terrorism through the National Legislation Program (Proglegnas) of the National Security Bill - Kristiyanto, Hasto; Widodo, Pujo; Putro, Resmanto Widodo (Budapest International Research and Critics University, 2021)
The development of an increasingly complex strategic environment today poses various forms of threats that are diverse and affect national security, including the threat of terrorism. Terrorism has become an important record in national security and has even been reported by the United Nations as a threat that the world needs to be aware of. In facing the changing trend and dynamic development of security threats, a comprehensive and effective countermeasure is needed through the role of state apparatus and other components of the nation, including the legal system. To build a national security system, it is necessary to use the national legal system as a basis for taking comprehensive and effective action on all threats and crimes that undermine national security and stability. The establishment of our country's national security system has been proposed in the National Security Bill, but there are still some obstacles, but the latest development of the national security bill, namely the bill has become one of the agenda of the National Security Bill. Legislation Plan (PROLEGNAS) for the period 2019-2024. The urgency of the National Security Bill in countering terrorism in Indonesia in this study uses a qualitative method with the type of literature study. Through the studies conducted, although there are still differences of opinion and views from experts and practitioners on the concept of national security, the urgency of the National Security Law is appropriate and expected to be a comprehensive legal system in its field.